Induction of drought tolerance by inoculation of Bacillus aryabhattai on sugarcane seedlings - May, André; Moreira, Bruno Rafael Almeida [UNESP]; Mascarin, Gabriel Moura; Viana, Ronaldo Silva [UNESP]; Santos, Michelli Souza; Silva, Evandro Henrique Figueiredo Moura; Ramos, Nilza Patrícia; Soares De Melo, Itamar (UNESP - Universidade Estadual Paulista, 2019)
In twenty-first century, free-living endophytic and rhizosphere-competent microbes have become breakthrough strategies to meet global demands for sustainable foods and renewable fuelstocks owing to their great potential to produce stress-tolerant food and energy crops. Here, we investigate how Bacillus aryabhattai could mitigate water stress by drought in sugarcane seedlings. Briefly, the sugarcane genotypes, namely IAC91-1099 and RB85-5156, both exposed to cells-centrifuged B. aryabhattai suspension at 1x108 CFU mL-1 and non-treated were developed under irrigation regimes of 0, 7, 14 and 21 days to simulate different degrees of soil moisture content. The osmotolerant bacterium remarkably enhanced development of aboveground structures and root system, mainly in irrigated seedlings of IAC91-1099. Clearly noted that microbial metabolism depends on genotype and soil water potential to promote plant growth. This bacterium probably enabled sugarcane plants in early phenological stages to cope with water deficit by regulation of plant growth hormones along with solubilization of nutrients. Of particular importance, the bacterium exerted more pronounced effects by conferring drought tolerance at 7 and 14 days irrigation interval, irrespective of sugarcane genotype, which also translated into increased biomass of shoots and roots. Microbial degradation of ethylene precursors exuded in rhizosphere could reasonably explain why B. aryabhattai-associated seedlings developed deeper root systems to uptake water and nutrients and, conse-quently, allocating larger amounts of dry matter to shoots. Collectively, our findings provide relevant insights on the beneficial effects of the cacti-associated B. aryabhattai in alleviating the harmful effects of drought stress in seedlings and contribute to increasing our understanding of the phenotypic outcomes from the interaction be-tween sugarcane genotypes and a beneficial rhizobacterium. Hence, this bacterial inoculant forms a low-cost and ecologically sound strategy to enhancing drought stress tolerance in sugarcane crops planted in water-limited zones in Brazil.
Keywords: Morphological change; Plant growth-promoting bacterium; Rhizobacterium; Saccharum spp.; Water stress